Accuracy of imaging modalities for adnexal torsion: a systematic review and meta‐analysis. (23rd July 2020) - Wattar, B; Rimmer, M; Rogozinska, E; Macmillian, M; Khan, KS; Al Wattar, BH
Abstract : Background: Adnexal torsion (AT), a serious gynaecological emergency, often presents with non‐specific symptoms leading to delayed diagnosis. Objective: To compare the test accuracy of ultrasound, computed tomography (CT) and magnetic resonance imaging (MRI) to diagnose AT. Search strategy: We searched EMBASE, MEDLINE and Cochrane CENTRAL until December 2019. Selection criteria: Studies reporting on the accuracy of any imaging modality (Index Test) in female patients (paediatric and adult) suspected of AT compared with surgical diagnosis and/or standard clinical/radiological follow‐up period until resolution of symptoms (Reference Standard). Data collection and analysis: We assessed study quality using QUADAS‐2. We conducted test accuracy meta‐analysis using a univariate model or a hierarchical model. Main results: We screened 3836 citations, included 18 studies (1654 women, 665 cases), and included 15 in the meta‐analyses. Ultrasound pooled sensitivity ( n  = 12, 1187 women) was 0.79 (95% CI 0.63–0.92) and specificity was 0.76 (95% CI 0.54–0.93), with negative and positive likelihood ratios of 0.29 (95% CI 0.13–0.66) and 4.35 (95% CI 2.03–9.32), respectively. Using Doppler with ultrasound ( n  = 7, 845 women) yielded similar sensitivity (0.80, 95% CI 0.67–0.93) and specificity (0.88, 95% CI 0.72–1.00). For MRI ( n  = 3, 99 women), the pooled sensitivity was 0.81 (95% CI 0.63–0.91) and specificity was 0.91 (95% CI 0.80–0.96). A meta‐analysis for CT was not possible with two case‐control studies and one cohort study ( n  = 3, 232 women). Its sensitivity range was 0.74–0.95 and specificity was 0.80–0.90. Conclusions: Ultrasound has good performance as a first‐line diagnostic test for suspected AT. Magnetic resonance imaging could offer improved specificity to investigate complex ovarian morphology, but more evidence is needed. Tweetable abstract: To investigate adnexal torsion, ultrasound is a good first‐line diagnostic test with a pooled sensitivity of 0.79 and specificity of 0.76. Tweetable abstract: To investigate adnexal torsion, ultrasound is a good first‐line diagnostic test with a pooled sensitivity of 0.79 and specificity of 0.76.